INFARTO AGUDO DO MIOCÁRDIO ATENÇÃO DO ENFERMEIRO FRENTE A INDIVÍDUOS COM SINTOMAS - Scherer, Cristiane; Sandri, Andréia; Rosanelli, Cleci S. P.; Jesus, Bianca S. d. (Salão do Conhecimento, 2013)
Resumo